Exploring the Efficacy of Quranic Arabic Corpus as an Instructional Tool to Enhance Nahwu Proficiency among UIN Jakarta Development Madrasah Students - Achmad Fudhaili (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2024)
This research aims to solve problems in Nahwu learning; the many students who find it difficult to apply Nahwu rules in Arabic texts, especially the Koran, require teachers to innovate information technology-based learning. Based on this, researchers will research the effectiveness of using the Quranic Arabic Corpus based on teaching materials and online learning media in making it easier for students to understand and analyse Nahwu grammar in Arabic. This research uses a quantitative approach with a True-Experimental design (experimental and control groups). The population of this research is students in the Aliyah class of the Fisabilillah Bekasi Islamic Boarding School. The sampling technique used was Simple Random Sampling Probability Sampling, with 36 students consisting of 18 experimental and 18 control class students. The data was calculated using the instrument validity test, the t-test normality test to prove the researcher's hypothesis and the N-Gain test to see the level of effectiveness. The data analysis technique uses hypothesis testing with the T-test. The research results were seen from how big the difference was in the post-test results after using the Quranic Arabic Corpus between the experimental group and the control group and the students' responses based on the questionnaire distributed during the research. The results of this research are as follows: First, there is a statistical difference in the average scores in the experimental group and the control group in Nahwu learning after using the Quranic Arabic Corpus; there is a significant difference, namely 67.22 for the experimental class while, for the control class it is 44.72. The two calculated